CHEMICAL CONTROL OF Conyza canadensis (L.), IN MIXTURES OF HERBICIDES WITH GLYPHOSATE IN COFFEE CROP - da Silva, Carlos Alberto; Miranda, Gustavo Rabelo Botrel; Alves, Alberto Donizete; Goulart, Roseli dos Reis (Coffee Science - ISSN 1984-3909, 2018)
The plants invasion of Conyza genus has occurred in several regions in Brazil and in the world, due to the selection caused by the continuous use of herbicides with the same active, causing losses in production. This work aims to evaluate the association of herbicides in the control of C. canadensis. The trial was carried out on a farm, in MG, in a Mundo Novo coffee plantation, in a randomized block design (RBD), with 7 treatments and 4 replications, totalizing 28 plots. The treatments were composed by CTU (no application), Glyphosate 1440g i.a ha-1, Glyphosate 1440g i.a ha-1 + Ethyl Chlorimuron 25g i.a ha-1, Glyphosate 1440g i.a ha-1 + Methyl Metsulfuron 6g i.a ha-1, Glyphosate 1440g i.a ha-1 + Flumioxazine 100g i.a ha-1, Glyphosate 1440g i.a ha-1 + Ethyl Carfentrazone 32g i.a ha-1, Glyphosate 1440g i.a ha-1 + Saflufenacil 56g i.a ha-1. In all treatments, non-ionic Dash adjuvant was used in the proportion of 1% of the application volume. Ten evaluations were carried out using the scores criterion, where 1 means efficiency between 0 and 20%; 2 from 21 to 40%; 3 from 41 to 60%; 4 from 61 to 80%; 5 from 81 and 100%. It is concluded the treatment Glyphosate 1440g i.a ha-1 + Saflufenacil 56g i.a ha-1 presented superior results from the first evaluation, evolving until the conclusion of this experiment.